Does statin pre-treatment affect right atrial myocyte apoptosis in coronary artery bypass graft patients? An in-vivo pilot study - (:unkn) unknown (Turk Gogus Kalp Damar Cerrahisi Dergisi, 2014)
Background: This study aims to investigate the possible protective effects of statin pretreatment against right atrial myocyte apoptosis in patients undergoing coronary artery bypass grafting. Methods: Twenty-nine consecutive patients were included in the study. Group 1 patients (n=12; male: 83.3%) were initiated on atorvastatin 40 mg/day on the day of hospital admission and group 2 patients (n=17; male: 82.3%) did not receive statin therapy. Right atrial samples were taken before cardiopulmonary bypass and fixed in 10% neutral formalin. Immunoperoxidase staining and TUNEL method were performed to detect apoptotic cells. The immunostained active caspase-3 and proliferating cell nuclear antigen (PCNA) cells were counted using a light microscope. Results: The mean apoptotic index was significantly lower in endocardial (p=0.04) and epicardial layers (p=0.01) of group 1 patients compared to those of group 2. Myocardial layer values were similar between the groups (p=0.35). The mean PCNA index in any layers was not significantly different between groups. Conclusion: Statin pretreatment before CABG seems to diminish cardiac myocyte loss, providing an explanation for their beneficial effects seen after open heart surgery.
Keywords: Apoptosis; Coronary artery bypass grafting; Statin